Assessment on Elevated Serum Vitamin B 12 Level in Cancer Patients at Hiwa Hospital - Noori, Niann; Ramzi, Zhian S.; Saeed, Aveen Aveen H.; Omer, Kosar Kosar A.; Nore, Beston F. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Free circulating serum Vitamin B12 (Vit-B12) levels is mainly used for diagnosis the deficiency of cobalamin (Cbl). However, approximately 15% of patients have hypercobalaminemia (high Vit-B12 levels) without any existing consensus for its clinical implications.But elevated levels of serum Vit-B12 could be a sign of severe, even life-endangering diseases such hematologic complications and numerous tumour types. In this work, we shall evaluate the diagnostic values of elevated Vit-B12 levels in 50 cancer patients (solid cancer patients, non-solid cancer) with 36 healthy people as control. The data shows that the elevated Vit-B12 concentration in the cancer patients was attributed, at least partly, to the cancer type or stage. Interestingly,%50 of patients had Vit-B12levels much greater than the upper limit (>489pg/ml), while the 36 control samples (apparent healthy) had normal levels 100%, within the reference intervals (141pg/ml to 489 pg/ml). We have concluded that the elevated serum Vit-B12is not related to diet intake, but most likely result of malignant processes. This work emphasizes that the possible clinical course of hypercobalaminemia should be under attention in the diagnostic process of malignancies.
Keywords: Cobalamin; Leukemia; Biomarker; Solid Cancer; Circulating Vitamin B12